Progress and challenges in the clinical evaluation of immune responses to respiratory mucosal vaccines - Xuanxuan Zhang; Jialu Zhang; Si Chen; Qian He; Yu Bai; Jianyang Liu; Zhongfang Wang; Zhenglun Liang; Ling Chen; Qunying Mao; Miao Xu (Expert Review of Vaccines)
Introduction Following the coronavirus disease pandemic, respiratory mucosal vaccines that elicit both mucosal and systemic immune responses have garnered increasing attention. However, human physiological characteristics pose significant challenges in the evaluation of mucosal immunity, which directly impedes the development and application of respiratory mucosal vaccines.Areas Covered This study summarizes the characteristics of immune responses in the respiratory mucosa and reviews the current status and challenges in evaluating immune response to respiratory mucosal vaccines.Expert Opinion Secretory Immunoglobulin A (S-IgA) is a major effector molecule at mucosal sites and a commonly used indicator for evaluating respiratory mucosal vaccines. However, the unique physiological structure of the respiratory tract pose significant challenges for the clinical collection and detection of S-IgA. Therefore, it is imperative to develop a sampling method with high collection efficiency and acceptance, a sensitive detection method, reference materials for mucosal antibodies, and to establish a threshold for S-IgA that correlates with clinical protection. Sample collection is even more challenging when evaluating mucosal cell immunity. Therefore, a mucosal cell sampling method with high operability and high tolerance should be established. Targets of the circulatory system capable of reflecting mucosal cellular immunity should also be explored.